math

posted by .

Multiply
3x + 3
by
-4x2 + 4x – 2 (Points : 20)

  • math -

    (3x + 3)(-4x^2 + 4x - 2)
    -12x^3 + 12x^2 - 6x - 12x^2 + 12x - 6
    note that the 12x^2 and -12x^2 will cancel out, and we combine -6x and 12x:
    -12x^3 + 6x - 6

    hope this helps~ :)

  • math -

    (3x+3)(-4x^2+4x-2)=
    3x(-4x^2)+3(-4x^2)+3x(4x)+3(4x)+3x(-2)+
    +3(-2)=

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    -5(3x - 7) Sorry I meant this one:-4x2(3x2 - x + 1) *Your supposed to do the FOIL Method! -12x4 + 4x3 - 4x2
  2. Math

    How do I mutliply the following; (4x2+3x-3)(4x2+3x-3)
  3. Algebra

    Below is a "complete the square problem" from a math help site on the internet. This is the original problem. 4x2 – 2x – 5 = 0 Move the loose number over to the other side. 4x2 – 2x = 5 Divide through by whatever is multiplied …
  4. maths

    Using the digits 1, 2, 3 & 4 each once only, and as many +, -, x, / and brackets as you need, try to make as many different numbers as you can, starting at 0, 1, 2 .... Which is the first number that you cannot make?
  5. Math

    Using the digits 1, 2, 3 & 4 each once only, and as many +, -, x, / and brackets as you need, try to make as many different numbers as you can, starting at 0, 1, 2 .... Which is the first number that you cannot make?
  6. pre cal

    Factor completely: 3x^2(4x2 + 1)^8 + 64x^4(4x2 + 1)^7.
  7. Algebra

    1. What polynomial has a graph that passes through the given points?
  8. Pre cal

    Fine a third degree polynomial function f(x) with real coefficients that has 4 and 2i are zeros and such that f(-1) =-50 4 21 -2i (x-4)(x-2i)(x+2i) (x-4)(x2+4) x3-16+4x-4x2 (x3-4x2+4x-16) -50=a(-1-4-4-16) -50=.25 a=2 Not understanding, …
  9. Continuity Calculus Help

    9.0/1 points | Previous Answers SSTCalc6 2.3.046.My Notes Question Part Points Submissions Used Let f(x) = 4x2 if x > 2 4x + 3 if x ≤ 2. Show that f is continuous from the left at x = 2, but not from the right. lim f(x) = n→2− …
  10. Math

    Prove 3(x+1)(x+7)-(2x+5)² is never positive So, 3(x+1)(x+7)-(2x+5)(2x+5) =3(x²+8x+7)-(4x²+20x+25) =3x²+24x+21-4x²-20x-25 =-x²+4x-4

More Similar Questions